Blossom - Butler ,Dale (Nelson Australia South Melbourne, 1994)
Blossom by Dale Butler is a poignant coming-of-age story centered around the life of a young woman navigating love, loss, and self-discovery. The novel explores themes of personal growth, family dynamics, and resilience, set against the backdrop of a small, tight-knit community.